Association between single nucleotide polymorphisms in estrogen receptor 1/2 genes and symptomatic severity of autism spectrum disorder. (November 2018) - Doi, Hirokazu; Fujisawa, Takashi X.; Iwanaga, Ryoichiro; Matsuzaki, Junko; Kawasaki, Chisato; Tochigi, Mamoru; Sasaki, Tsukasa; Kato, Nobumasa; Shinohara, Kazuyuki
Highlights: We investigated the association between estrogen receptor gene polymorphisms and symptom severities of autism in Japanese sample. Symptomatic severities of social interaction and emotional regulation were linked to genetic polymorphisms of estrogen receptor 1 and 2 respectively. There were signs of ethnic variation in the influences of genetic polymorphisms tested on autism symptom severities. Abstract: Background: Previous studies on etiology of autism spectrum disorders (ASD) have shown strong contribution of hereditary factors. On the basis the heterogeneity in ASD symptoms, it is highly possible that each independent domain of ASD symptom is linked to a different set of genetic risk factors. However, few empirical investigations have been carried out to examine this hypothesis. Aims: The aim of the present study was to investigate the association between single-nucleotide polymorphisms (SNPs) in estrogen receptor genes, which several previous studies have identified as potential risk factors of ASD, and the severity of each independent aspect of ASD symptom within an Asian clinical sample. Method and procedures: We investigated the association between severities of four ASD symptoms (Social Communication, Social Interaction, Stereotypies and Sensory Abnormalities, and Emotional Regulation) measured by childhood autism rating scale and SNPs in genes of estrogen receptor 1 and 2, ESR1 rs11155819 and ESR2 rs1152582, in 96 Japanese individuals with ASD. Outcomes and results: The analysis revealed that severities in the impairment of social interaction and emotional regulation were linked to SNPs in ESR1 rs11155819 and ESR2 rs1152582, respectively. The effect of genotype was not observed for the other aspects of ASD symptoms. Conclusions and implications: These findings support our contention that the severity of each ASD symptom domain is determined by a distinct set of genetic risk factors.